Breeding Stud Sheep - Long, Murray (Collingwood Land Links, 2008)
Many mistakes are made by new stud breeders and in today's climate these can be expensive and ultimately result in a loss of enthusiasm for new breeders. This book will explain all aspects of stud breeding, from the decision to establish a sheep stud through to purchasing breeding stock, advertising, promoting and selling stud stock. This book will help new breeders avoid the pitfalls and show how to succeed in what is ultimately a tough, but very rewarding, industry.
Include Index, Appendix and Illustration
Keywords: Sheep--Breeding -- Sheep breeds -- Australia